SUBJECT: ENGLISH PHONOLOGICAL CHALLENGES AS FACED BY KISANGANI IBTP THIRD YEAR’S UNDERGRADUATE STUDENTS. - Cimwanga, Arthur; Olonga , Sylvie (IJRDO- Journal of Educational Research, 2022)
The topic has been chosen from an unfortunate observation made on the mispronunciation of English words by G3 IBTP students on the field. It is inspired by a poor experience as teacher of English at IBTP Kisangani mainly on the phonological level